Pengaruh Pemberian Ekstrak Biji Klabet (Trigonella foenum-graecum L.) Terhadap Perkembangan Kelenjar Mamae Tikus Putih Betina Galur Wistar - Agustini, Kurnia; Wiryowidagdo, Sumali; Kusmana, Dadang (UI Scholars Hub, 2007)
Phytoestrogen is the chemical compound contains in plant which has estro-genic like effect. Estrogen has important function on woman’s sexual organ, such as proliferation of uterine and vaginal cornification. Phytoestrogen are weak agonists for estrogen and illicit statistic significantly increases in uterine wet weight, at definite dose, in uterothrophic bioassay. Biji Klabet or Fenugreek seed (Trigonella foenum-graecum L.) contains steroidal sapogenins such as diosgenin, tigogenin, gitogenin, yamogenin and trigoneoside, that suspected having an estrogen-like ef-fect or as phytoestrogen. The aim of this research was to investigate the estrogenic effect of fenugreek’s ethanolic extract in ovariectomized and immature rats models. These models represent the climacteric/menopause phase, where estrogen level is very low because ovary produces no estrogen. The testing animals were divided into normal group, ovariectomized control group, estradiol control group and three level doses of fenugreek extract (30mg/200gBW; 60mg/200gBW and 120mg/200gBW). The result indicated that start on 60mg/200gBW, fenugreek extract significantly could increasing mammary gland proliferation. Empirically fenugreek containing diosgenin, that caused breast enhancement. This research showed that treatment with fenugreek extract can caused proliferation of mammary gland, both on imma-ture and ovariectomized rats.